2022
DOI: 10.32322/jhsm.1167524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors and outcomes associated with mortality after hip fracture surgery in eldery patients

Abstract: Objective: In this retrospective study, it was aimed to compare mortality related risk factors and outcomes in patients who underwent proximal femoral nail and partial hip prosthesis for hip fracture. Material and Method: In our study, a total of 618 patient files who underwent hip fracture operations, including partial hip replacement (n=350) and proximal femoral nail (n=268) were retrospectively analyzed. Age, gender, fracture side, cause, type of fracture, type of operation, blood transfusion, hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the authors found that postoperative, life-threatening complications were more common in the BHA group. In their study involving 618 patients, İpek et al 15 found no difference between the 1-year survival rates of patients who underwent PFN and BHA. In the current study, the 1-year mortality rate was 26.1% in the BHA group and 25.2% in the PFN group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the authors found that postoperative, life-threatening complications were more common in the BHA group. In their study involving 618 patients, İpek et al 15 found no difference between the 1-year survival rates of patients who underwent PFN and BHA. In the current study, the 1-year mortality rate was 26.1% in the BHA group and 25.2% in the PFN group.…”
Section: Discussionmentioning
confidence: 90%
“…Similar results have been reported in previous studies. 15 Pincus et al 16 analyzed a cohort of 42,230 Canadians in terms of time from diagnosis to surgery. They reported that those who underwent surgery within 24 h of presenting with hip fractures had a lower 30-day mortality rate.…”
Section: Discussionmentioning
confidence: 99%